TAFSIR AL-QURAN DALAM NASKAH [MAJAZ]: Studi Filologis dan Analisis Isi - Mujahid, Ahmad (Jurnal Ilmiah Ilmu Ushuluddin, 2012)
In South Kalimantan, the manuscripts on tafsir up to this present were not found. Thetopics were dominated by the sufism and jurisprudence. This fact, actually become thegeneral phenomena in Indonesia. The manuscript was discussed here speak aboutbalaghah knowledge , especially on Majaz. By this manuscript, the writer want tomake a relation between manuscript of non-tafsir and the tafsirs study. Here, thewriter use the filology approach, while for the tafsir, writer analyzed the verses in thetext using the tafsir approach. Actually, the verses were qouted here only five verses, evenit part of the verses. The qouted verses here were examples of the quran than containedthe study of majaz. The explanation of writer on that verses of quran is a tafsiraccording to the writes.